Development of sandwich and label-free electrochemical immunosensor for detection of HER2 breast cancer biomarker - Lah, Zur Mira Azizah @ Nor Haiza (2018)
An electrochemical immunosensor for determination of HER2 biomarker was developed using two different types of immunoreaction, which are label-free and sandwich assay. The fabrication of label-free immunosensor involved several steps; (1) pre-treatment of screen printed carbon electrode (SPCE) (2) the binding of primary anti-HER2 antibody to pre-treated SPCE via EDC/NHS (3) bovine serum albumin (BSA) blocking (4) the binding of HER2 antigen (5) electroanalytical performance of the label-free immunosensor. While, in sandwich immunosensor, lead sulphide quantum dots coated with secondary antibodies (Ab2-PbS QDs) were used as a label and the fabrication involved additional several steps which were; (1) synthesis and bioconjugation of PbS QDs with secondary onto-HER2 antibody (2) the sandwich of Ab2-PbS QDs onto label-free immunosensor (3) acid dissolution of Pb2+ from label and detection via square wave voltammetry (SWV). The electrochemical properties of the developed immunosensors were analysed by cyclic voltammetry (CV) and electron impedance spectroscopy (EIS) using Fe(CN)6 -3/-4 as a redox probe. Under optimal condition, label-free and sandwich immunosensors were assessed by using differential pulse voltammetry (DPV) and SWV, respectively. The analytical performances revealed that both immunosensor give satisfactory sensitivity, selectivity and reproducibility towards HER2 cancer biomarker. For a linear range of 0.04- 2.0 ng/ml of label-free immunosensor, the limit of detection obtained was 0.01 ng/ml while for sandwich immunosensor, the limit of detection obtained was 1.1 ng/ml for a linear range of 2.0-10 ng/ml Furthermore, excellent recovery also obtained in human serum sample for both label-free and sandwich immunosensor. It was discovered that the recovery percentage of HER2 antigen in sandwich immunosensor was 102.06 % with RSD percentage of 7.51 %, while for label-free immunosensor, the percentage recovery is 97.10 % with RSD percentage of 10.89 %.